PRAGMATIC COMPETENCE CONSTRUCT IN SECOND LANGUAGE ACQUISITION: CRITICAL THEORETICAL AND PEDAGOGICAL PERSPECTIVES IN LANGUAGE TEACHING - Santos, Rafael Ibe (IJIET (International Journal of Indonesian Education and Teaching), 2025)
Drawing from literature on language and interlanguage pragmatics as well as education and business, this conceptual paper presents the current realities in second language learning and instruction and argues for the need to align collegiate second language acquisition curricula that emphasize linguistic and pragmatic competence. Such revision is consistent with the need to prepare college students to meet the critical demands of multi-context communication, which necessitates a deliberate teaching of pragmatic competence.  More than the typical cognitive and technical skills, both local and global job markets need wide-ranging sets of communication-related competences as these affect meaning-making and quality of relationships, particularly in the workplace. Acquisition or enhancement of these skills paves the way for career, business, and life success. Said competencies also highlight the value of social or sociocultural skills as well as internal attributes that are critical in fostering healthy relationships and fruitful interaction. Both sets of skills speak of a person’s appropriateness in terms of use of pragmalinguistic and sociopragmatic resources and norms in communication, in addition to the aptness of understanding of linguistic and non-linguistic codes. Ultimately, these skills all boil down to pragmatic competence, which is needed in a balanced second language teaching approach.